THE OKHOTSK VOLCANIC OCEANIC PLATEAU - Bogdanov N.A.; Dobretsov N.L. (My University, 2002)
The Okhotsk-Sea plate is interpreted as an old volcanic oceanic plateau bounded by right-lateral strike-slip faults in the east and west, a Middle Cretaceous subduction zone in the north, and by a zone of ongoing subduction of the Pacific plate beneath Eurasia in the south. Remnant Middle Jurassic-Lower Cretaceous oceanic crust is exposed on the plate margins (eastern Sakhalin, Taigonos Peninsula, Kuyul Ridge, and Omgon Peninsula in western Kamchatka) in accretionary prisms. The South Okhotsk deepest oceanic basin located south of the plate is most likely of oceanic origin and, like the whole Okhotsk-Sea plate, can be interpreted as the largest relic fragment of the Late Cretaceous Kula oceanic plate. A volcanic uplift in the center of the Okhotsk-Sea plate is identified as the Okhotsk volcanic plateau. The plateau shares some geophysical characteristics with other volcanic plateaus, such as Ontong Java, Shatsky Rise, Hess, etc. It apparently emerged north of the mid-ocean ridge, within the Kula plate, as a result of the latest Jurassic-earliest Cretaceous mantle plume eruption beneath the Kula-Pacific-Faralon triple junction. As a result of the northward motion of the Kula plate with the Okhostk plateau as its part, the latter jammed the subduction zone beneath the Okhotsk-Chukchi volcanoplutonic belt in the latest Turonian. Similar jammed subduction zones are known in the vicinity of many accretionary fold-thrust belts.